How to shape a business service to its customers' exact needs: a hostel in Lisbon - Faísca, H. (2015)
The present business plan intents to analyze the financial attractiveness of creating a Hostel within Lisbon and targeting a service proportionate to guests' needs. That is, a service design based in the importance customers attribute to each offer. As observed, the market at Lisbon reflects a very competitive field where Hostels provide high quality services for low prices. During the low season (October-April), money is lost due to low occupancy rates. Nevertheless, profit resulting from the high season (May-September) is enough to null the negative results of the low season and still present a positive result at the end of the year. Financially, the evaluation outputs a NPV of 42 726€, IRR of 25.64% and Payback period of three years and four months. With vital indicators pointing towards a profitable business, the conclusion is that, based on the analysis performed, such a Hostel is financially viable.